Assessing HPV vaccine coverage in Australia by geography and socioeconomic status: are we protecting those most at risk? - Bianca Barbaro; Julia M.L. Brotherton (Elsevier, 2014)
Abstract Objective: To determine whether HPV vaccine coverage in 12-13‐year‐olds varies by geographical area, remoteness and ecological level indicators of socioeconomic status (SES). Method: Data from the National HPV Vaccination Program Register (NHVPR) were analysed at Statistical Local Area (SLA) level, by the Index of Relative Disadvantage (IRSD) and the Australian Standard Geographical Classification Remoteness Structure. Results: Nationally, 73% of females aged 12-13 years in 2007 were fully vaccinated against HPV. Coverage in low SES areas (71.5%) was 4.1 percentage points lower than coverage in high SES areas (75.6%). Uptake of the first two doses was higher in the very remote parts of Australia (dose 1 - 88.5%, dose 2 - 81.8%) than in major cities (dose 1 - 83.4%, dose 2 - 80.2%), but not for dose 3 where coverage in major cities was 3% higher (73.6% versus 71.4%). Conclusion: Notifications of HPV vaccine doses delivered to females aged 12-13 through schools suggest a high and relatively equal uptake across socioeconomic groups. Females in remote regions have the highest uptake of dose 1 but are least likely to complete the course. This may be due to particular challenges in vaccine delivery to residents of remote areas.